REVERSE LOGISTICS OF LIVESTOCK WASTE BETWEEN PRODUCERS AND SPECIALISED STATE-OWNED ENTERPRISES - Dubnevych Ю. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2025)
This scholarly article addresses the issues of reverse logistics for livestock waste, which plays a crucial role in ensuring effective waste management, reducing the negative environmental impact, and supporting the sustainable development of the agricultural sector. The principal stages of the logistics process, including the collection, transportation, processing and disposal of waste, are analysed. Particular attention is paid to the interaction between livestock producers and specialised state-owned enterprises engaged in waste processing. The author examines the organization of reverse logistics for livestock waste between producers and specialized state enterprises. The key stages of the reverse material flow - collection, transportation, processing, and disposal of biological waste - are analyzed. The main challenges and barriers to implementing effective logistics schemes in this field are identified. Special attention is given to the environmental and economic aspects of reverse logistics, as well as potential methods to optimize processes using modern technologies and state regulation. The article highlights the key problems nd challenges faced by the participants of the logistics chain, such as the organisation of an efficient system for waste collection and transportation, adherence to environmental safety regulations, and the optimisation of processing costs. Additionally, it considers the issues of the regulatory and legal framework governing reverse logistics for livestock waste and examines the potential for innovative technologies to enhance processing efficiency. Drawing on the conducted research, the study presents conclusions regarding opportunities to enhance existing approaches to livestock waste management and offers recommendations to foster collaboration between producers and state-owned enterprises. The research findings have significant implications for professionals in logistics and agriculture, as well as for government policymakers responsible for environmental regulation.